2019
DOI: 10.1111/1365-2656.13025
|View full text |Cite
|
Sign up to set email alerts
|

Interaction engineering: Non‐trophic effects modify interactions in an insect galler community

Abstract: Theory suggests that non‐trophic interactions can be a major mechanism behind community stability and persistence, but community‐level empirical data are scarce, particularly for effects on species interactions mediated through changes in the physical environment. Here, we explored how ecosystem engineering effects can feed back to the engineer, not only modulating the engineer’s population density (node modulation) but also affecting its interactions with other species (link modulation). Gall induction can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 49 publications
1
14
0
2
Order By: Relevance
“…The presence of galls and their effects on host plant morphology, architecture, and performance have been previously investigated in the literature , but no study has shown that galls might facilitate ecosystem engineering when galled leaves are rolled and act as shelters for secondary colonization. After experimental manipulation of leaf galls in the shrub Baccharis dracunculifolia, Barbosa et al (2017) have shown increased parasitism in the gall Baccharopelma dracunculifoliae and reduced connectance, evenness, and robustness of arthropod food webs, indicating the central role gallers have in interaction engineering (Barbosa et al, 2019). Our study reinforces and highlights this important role, as gall presence facilitated ecosystem engineering, changing community composition, richness, and biomass.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…The presence of galls and their effects on host plant morphology, architecture, and performance have been previously investigated in the literature , but no study has shown that galls might facilitate ecosystem engineering when galled leaves are rolled and act as shelters for secondary colonization. After experimental manipulation of leaf galls in the shrub Baccharis dracunculifolia, Barbosa et al (2017) have shown increased parasitism in the gall Baccharopelma dracunculifoliae and reduced connectance, evenness, and robustness of arthropod food webs, indicating the central role gallers have in interaction engineering (Barbosa et al, 2019). Our study reinforces and highlights this important role, as gall presence facilitated ecosystem engineering, changing community composition, richness, and biomass.…”
Section: Discussionsupporting
confidence: 71%
“…Results were even stronger when shelters created by galls were unoccupied. Arthropod communities associated to galls are not discrete ecological communities and interactions with other members might occur via habitat availability (Barbosa et al, 2017(Barbosa et al, , 2019. Leaf rolling by gallers and changes in leaf morphology and plant architecture are frequent, but facilitation of shelter creation by gallers has been rarely studied, although many galls curl leaves during development (Harris & Pitzschke, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations